Pharmacological postconditioning effect of muramyl dipeptide is mediated through RIP2 and TAK1 - Sicard, Pierre (Oxford University Press, 2009)
AIMS: Despite their ability to cause septic shock and myocardial dysfunction, components of Gram-negative bacterial cell walls, like lipopolysaccharide, have been shown in numerous studies to induce myocardial protection during ischaemia–reperfusion injury. Muramyl dipeptide (MDP) is another such component recognized by an intracellular receptor, nucleotide-binding oligomerization domain 2. Receptor activation leads to intracellular signals through receptor interacting protein-2 (RIP2) and tumour growth factor-β-activated kinase-1 (TAK1). However, little is known about the RIP2/TAK1 pathway in the heart. The aim of this study was to determine whether the RIP2/TAK1 pathway has a cardioprotective role in a mouse model of myocardial infarction. METHODS AND RESULTS: We isolated and subjected wild-type (WT) and RIP2(−/−) mouse hearts to 30 min of global ischaemia and 120 min of reperfusion with or without perfusion of MDP (10 µg/mL) before or after the ischaemic period and determined the infarct size. We examined activation of the TAK1/nuclear factor κB (NFκB) signalling pathway. The effect of TAK1 inhibition on MDP-induced cardioprotection was also evaluated. Exposure to MDP during reperfusion significantly reduced infarct size in WT hearts (from 51.7 ± 5.6% in control to 38.1 ± 6.7%, P < 0.05), but not in RIP2(−/−) hearts or in WT hearts with coincident pharmacological inhibition of TAK1. MDP treatment significantly increased the levels of p-TAK1 and p-JNK (Jun N-terminal kinase) and led to NFκB activation via phosphorylation and degradation of IkappaB in the WT, but not in the RIP2(−/−), myocardium. CONCLUSION: These results indicate that MDP at reperfusion induced cardioprotection through an RIP2/TAK1-dependent mechanism.